NILAI PENDIDIK DALAM PENDIDIKAN AGAMA ISLAM (KAJIAN FILSAFAT PENDIDIKAN ISLAM) - Pranata, Hamdi (HIKMAH: JURNAL PENDIDIKAN AGAMA ISLAM, 2022)
Educators are people who play a very important role in educating the nation's children, when talking about educators what comes to our heads are adults who guide and give us something we don't know yet. This study aims to describe the value of educators in Islamic religious education in the Study of Islamic Education Philosophy. The research method uses literature study research, which is a series of activities related to methods of collecting library data, reading, analyzing and managing information obtained from various literacy sources. The results of the study obtained an explanation regarding the value of educators in Islamic religious education Philosophical Studies of Islamic Education which are divided into five classifications based on sources from the Al-Qur'an, Hadith, the opinions of scholars and educational figures. It is hoped that future researchers will be able to study and develop the concept of educators even better by adjusting to current developments in information and communication technology or the times.